“A Real Bucket of Worms”: Views of People Living with Dementia and Family Members on Supported Decision-Making - Sinclair, Craig (J Bioeth Inq, 2019)
Supported decision-making has been promoted at a policy level and within international human rights treaties as a way of ensuring that people with disabilities enjoy the right to legal capacity on an equal basis with others. However, little is known about the practical issues associated with implementing supported decision-making, particularly in the context of dementia. This study aimed to understand the experiences of people with dementia and their family members with respect to decision-making and their views on supported decision-making. Thirty-six interviews (twenty-one dyadic and fifteen individual) were undertaken with fifty-seven participants (twenty-five people living with dementia and thirty-two family members) across three states in Australia. Interpretative Phenomenological Analysis (IPA) was used as the methodological approach, with relational autonomy as a theoretical perspective. We identified two overarching themes relating to participants’ experiences with decision-making: “the person in relationship over time” and “maintaining involvement.” Participant views on the practical issues associated with supported decision-making are addressed under the themes of “facilitating decision-making,” “supported decision-making arrangements,” “constraints on decision-making,” and “safeguarding decision-making.” While participants endorsed the principles of supported decision-making as part of their overarching strategy of “maintaining involvement” in decision-making, they recognized that progressive cognitive impairment meant that there was an inevitable transition toward greater involvement of, and reliance upon, others in decision-making. Social and contextual “constraints on decision-making” also impacted on the ability of people with dementia to maintain involvement. These themes inform our proposal for a “spectrum approach” to decision-making involvement among people living with dementia, along with recommendations for policy and practice to assist in the implementation of supported decision-making within this population. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11673-019-09945-x) contains supplementary material, which is available to authorized users.